Manajemen kurikulum Cambridge di Madrasah Muallimin Muhammadiyah Yogyakarta - Ramadhanur Putra (Universitas Pendidikan Indonesia, 2026)
Understanding the implementation of the international curriculum in the context of Islamic education is especially important, especially in madrasas that integrate the Cambridge curriculum with the Islamic education system. This study aims to analyze the Cambridge curriculum management process in the Muallimin International Class (MIC) program at Madrasah Muallimin Muhammadiyah Yogyakarta. The method used in this research was a descriptive qualitative approach, with data collected through interviews, direct observation, and documentation. Data were obtained from key informants, including the Cambridge curriculum development team, teachers, and MIC program students. The results of the study show that curriculum management in this madrasah is running well, from thorough planning and effective organization to implementation using a student-centered learning approach to transparent evaluation. However, challenges in integrating the Cambridge curriculum with the national curriculum and ISMUBA remain to be addressed. This study is expected to contribute to the development of an international curriculum for Islamic educational institutions, especially madrasah.